A pesticide composition - Basri, Mahiran; Md. Jadi, Nur Faizlin; Omar, Dzolkhifli; Salleh, Abu Bakar; Abdul Rahman, Mohd Basyaruddin; Raja Abdul Rahman, Raja Noor Zaliha; Abd. Malek, Emilia (2010)
A pesticide composition comprising 0.2 to 5% w/w of azadirachtin; 20 to 80% w/w of aqueous medium; 5 to 50% w/w of surfactants mixture including an orgnosilicone and a non-ionic surfactant; and an oil phase of 1 to 20% w/w.